Seeking to Do What’s Best for Baby: - Karen Jagiello (Grounded Theory Review: An International Journal)
The purpose of this classic grounded theory study was to develop a theory of how rural breastfeeding women respond to their main concern associated with exclusive breastfeeding. Exclusive breastfeeding is recommended for infants through the first six months of life. Mothers living in rural U.S. communities exclusively breastfeed less frequently than their urban counterparts. The theory Seeking to Do What’s Best for Baby emerged from the data and describes the process that mothers work through to do what is best for their baby. The theory consists of a temporal three-stage process: pre-pregnancy nescience, working through, and succeeding or surrendering. The process is influenced by evolving internal conditions and basic social processes which account for the variation in the pattern of behavior. The results of this study begin to fill the gap in knowledge about the choices made by mothers to exclusively breastfeed to six months or to end exclusive breastfeeding.